DESIGN OF DATABASE EXAMS PROBLEM COLLECTING IN STMIK JAKARTA STI & K - Pradhitya Rama Dimas (Jurnal Sistem Informasi, 2008)
Trials are things can not be separated from the world of education, especially in STMIK Jakarta STI & K, so the matter was set to be routine for lecturers. Therefore, in the hope to facilitate these activities, the author makes "Build Database Design Question Bank STMIK Jakarta STI & K", where with this, teachers can organize and select questions for the exam easily and quickly.